Permainan Tradisional Menyentuh Bola terhadap Kemampuan Throw In Permainan Sepakbola - Wawan Syafutra; Hengky Remora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine whether there is a traditional game of touching the ball on the ability to throw in a soccer game at SMK Yadika Lubuklinggau. The research method used in this study is a true experimental experimental design category for the control group pretest posttest category. That is by conducting a preliminary test and a final test with a population of 120 people. From this population, a sample of 60 male students was taken. The sample was divided into two groups, namely the experimental group and the control group with each group totaling 30 people. The data collection technique used in this research is the throw-in test technique, the data obtained from the results of the throw-in test, is analyzed using t-test statistics. Based on the results of data analysis, it was found that there was a significant effect of traditional game practice on touching the ball on the ability to throw in soccer games Keywords : Touching the ball, Throw in